Synthesis of hybrid nanosheets of graphene oxide, titania and gold and palladium nanoparticles for catalytic applications - Papa, Letizia (2017)
Nanocatalysis has emerged in the last decades as an interface between homogeneous and heterogeneous catalysis, offering simple solutions to problems that conventional materials have not been able to solve. In fact, nanocatalyst design permits to obtain structures with high superficial area, reactivity and stability, and at the same time presenting good selectivity and facility of separation from reaction mixtures. In this work, we prepared hybrid structures comprising gold, palladium and silver nanoparticles (Au, Pd and Ag NPs), titanate nanosheets (TixO2), graphene oxide (GO), and partially reduced graphene oxide (prGO). We focused on bi- and tri-components hybrids, namely TixO2, M/(pr)GO and M/TixO2/(pr)GO (M = Au, Pd or Ag) and developed facile, versatile and environment-friendly preparation methods with an emphasis on control over physicochemical features such as size, shape and composition. In order to exploit the catalytic applications, we employed the reduction of 4-nitrophenol as a model reaction, followed by visible-light assisted oxidation of p-aminothiophenol (PATP). With these tests, we unraveled metal-support interactions and cooperative effects that render hybrid structures superior to their individual counterparts.